Nature in Verse in Cicero the Philosopher - Dal Chiele, Elisa (Ciceroniana On Line, 2023)
This contribution studies poetic citations in Cicero’s philosophical corpus, specifically those in which elements related to the natural environment appear. The analysis focuses on environmental aspects present in select quotations related to the theme of pain, where nature reflects the condition of physical and psychic suffering of the heroes, Philoctetes and Prometheus. The argument takes in verses from Accius’s Philoctetes, quoted in De finibus and Tusculanae disputationes, and Cicero’s translation from Aeschylus’s Prometheus Unbound (fr. 33 Bl.2), quoted in Tusc. 2, 23-25. The environment emerges as a hostile space that embraces the heroes’ cry of pain. At the same time, Cicero conjures a desolate and lonely landscape in his translation of a passage from Homer’s Iliad (6, 201-202 in Tusc. 3, 63; fr. 24 Bl.2), as the setting in which Bellerophon seeks consolation to his pain, condemning himself to silence and voluntary exile. Cicero does the same, after the death of his daughter Tullia (Att. 12, 15), in a literary gesture that brings together philosophy and autobiography through the theme of pain and loneliness.